U. FRANZEN, A. PÉREZ GÓMEZ, K. SHKAPICH (eds.) - Education of an architect: a point of view. Cooper Union School of Art & Architecture: 1964-1971 - Castellanos Gómez, Raúl (ZARCH, 2019)
Ulrich Franzen, Alberto Pérez-Gómez y Kim Shkapich (eds.)Education of an architect: a point of view. The Cooper Union School of Art & Architecture: 1964-1971Nueva York: The Monacelli Press, 1999, 364 páginas. Tapa blanda. Idioma: inglésISBN-10: 1580930409; ISBN-13: 978-1580930406